2004
DOI: 10.2105/ajph.94.4.619
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Long-Term Effects of the Safe Dates Program and a Booster in Preventing and Reducing Adolescent Dating Violence Victimization and Perpetration

Abstract: Safe Dates shows promise for preventing dating violence but the booster should not be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
371
3
15

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 441 publications
(399 citation statements)
references
References 34 publications
10
371
3
15
Order By: Relevance
“…The articles demonstrated that dating violence is a reality for both female and male adolescents in the countries in which the studies were carried out (4,9,(12)(13)18,20,(22)(23)30) . It is a phenomenon of great significance (4,9,(12)(13)18,20,22,30) , characterized by the perpetration and experience of various types of violence (9,(12)(13)20,(22)(23)(24)(26)(27)30) , on the part of both boys and girls (4,(11)(12)(13)32) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The articles demonstrated that dating violence is a reality for both female and male adolescents in the countries in which the studies were carried out (4,9,(12)(13)18,20,(22)(23)30) . It is a phenomenon of great significance (4,9,(12)(13)18,20,22,30) , characterized by the perpetration and experience of various types of violence (9,(12)(13)20,(22)(23)(24)(26)(27)30) , on the part of both boys and girls (4,(11)(12)(13)32) .…”
Section: Discussionmentioning
confidence: 99%
“…It is a phenomenon of great significance (4,9,(12)(13)18,20,22,30) , characterized by the perpetration and experience of various types of violence (9,(12)(13)20,(22)(23)(24)(26)(27)30) , on the part of both boys and girls (4,(11)(12)(13)32) . However, the studies showed gender-related differences regarding the types of violence experienced and perpetrated (4,(11)(12)(18)(19)22,25) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dates was selected as the cornerstone of the initiative because of its demonstrated and sustained primary and secondary preventive effects on multiple forms of dating violence for boys and girls (Foshee et al 1998(Foshee et al , 2004. Parents Matter!…”
mentioning
confidence: 99%